Engineering practice of wastewater treatment and reuse in lithium battery manufacturing - CHEN Jianhua (Gongye shui chuli)
In response to the characteristics of anode wastewater and cathode wastewater generated during the manufacturing process of lithium batteries, the design adopted the idea of classified collection, classified pretreatment, and then centralized biochemical treatment to treat the wastewater. Taking the lithium battery production wastewater of a new energy company in Guangdong as an example, this article briefly described the characteristics of the wastewater and the selection principles of anode wastewater and cathode wastewater treatment processes. Specific wastewater treatment processes were proposed on this basis. The anode wastewater was treated using a coagulation sedimentation+anaerobic+AOA+MBR process, and the treated effluent met the water pollutant discharge standards for newly established enterprises in Table 2 of Emission Standard of Pollutants for Battery Industry(GB 30484-2013) and the allowable discharge concentration limit for Class Ⅱ pollutants in Table 4 of the local standards of Guangdong Province of Discharge Limits of Water Pollutants(DB 4426-2001) before being discharged. The cathode wastewater was treated using the Fenton oxidation+coagulation sedimentation+UASB+secondary AO+MBR process. After the effluent was further treated by secondary RO/MVR, the recycled water and condensate reached the supplementary water standards in Table 1 of Water Quality for Heating and Air Conditioning Systems(GB/T 29044-2012) and the standards in Table 1 of The Reuse of Urban Recycling Water-Water Quality Standard for Industrial Uses(GB/T 19923-2005) before being reused. The concentrated water was evaporated and crystallized through the MVR system. Engineering practice had shown that the system operated stably, and the treated anode wastewater met the discharge standards, while the cathode wastewater met the reuse water standards, successfully achieving zero discharge.